2018
DOI: 10.3389/fnbeh.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks Mediating High-Level Mentalizing in Patients With Right Cerebral Hemispheric Gliomas

Abstract: Mentalizing is the ability to understand others’ mental state through external cues. It consists of two networks, namely low-level and high-level metalizing. Although it is an essential function in our daily social life, surgical resection of right cerebral hemisphere disturbs mentalizing processing with high possibility. In the past, little was known about the white matter related to high-level mentalizing, and the conservation of high-level mentalizing during surgery has not been a focus of attention. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 68 publications
(117 reference statements)
1
20
0
Order By: Relevance
“…Nakajima et al. demonstrated that high‐level mentalizing processing was associated with structural connectivity networks, which were influenced by the effect of right cerebral hemispheric glioma and its resection (Nakajima et al., 2018). Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nakajima et al. demonstrated that high‐level mentalizing processing was associated with structural connectivity networks, which were influenced by the effect of right cerebral hemispheric glioma and its resection (Nakajima et al., 2018). Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes that the functional ToM network is built on structural connectivity and can be disrupted by severing significant white matter connections. These results for high-level mentalizing were later confirmed in additional glioma patients, which also highlighted the superior longitudinal fasciculus and the fronto-striatal tract, whereas lower-level and face-based mentalizing was also associated with the OFC and the uncinate fasciculus (Nakajima et al, 2018a(Nakajima et al, , 2018b. Furthermore, a recent functional connectivity study (Fishman et al, 2014) found that in contrast to commonly held beliefs, persons with AS compared to NT controls exhibit increased and not decreased connectivity between the mentalizing and the simulation networks, giving rise to the intriguing hypothesis that persons with AS may suffer from overconnectivity and -as a result -a diminished functional segregation between these two networks.…”
Section: Neural Responsesmentioning
confidence: 61%
“…First, as mentioned in the preceding section, we cannot validate the usefulness of intraoperative monitoring of basic emotion compared to the control group. Although several previous reports have revealed the utility of intraoperative monitoring for right cerebral hemispheric function including emotional function, assessment of right frontal lobe function is still a challenge (Thiebaut de Schotten et al, 2005 ; Herbet et al, 2015 , 2016 ; Kinoshita et al, 2016 ; Nakajima et al, 2018 ). The usefulness of intraoperative monitoring of neuropsychological function should be considered from various aspects, such as the extent of resection, progression-free survival, overall survival, functional outcome, and postoperative social lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient’s group includes both low-grade and high-grade gliomas, although they are not biologically the same. However, several recent studies that investigated functional localization via awake brain mapping include both tumor types and obtain meaningful results (Gras-Combe et al, 2012 ; Saito et al, 2016 ; Nakajima et al, 2018 ; Puglisi et al, 2018 ; Rolland et al, 2018 ; Nakada et al, 2020 ). Additionally, we could not study the white matter tract, since we found only a few positive mapping sites at the subcortical level in our patient group.…”
Section: Discussionmentioning
confidence: 99%